2022
DOI: 10.1101/2022.02.06.479331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beta-cell Metabolic Activity Rather than Gap Junction Structure Dictates Subpopulations in the Islet Functional Network

Abstract: Network theory provides tools for quantifying communication within heterogeneous biological systems. Calcium-based imaging is a common technique used to analyze cellular dynamics and create functional networks. However, the use of functional networks in understanding the underlying biological structure, formed by physical connections, has not been well investigated. The islet of Langerhans is a biological system with relatively simple architecture that affords the opportunity for high-fidelity experimental and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…We observed a high level of synchrony or correlation between voltage time-courses of islet electrodes, which are qualitatively similar to the synchrony in calcium measurements between beta-cells that has been previously reported and depends on gap junction coupling (23). Our network analysis demonstrated that islets have synchronized electrical activity (Figure 5B).…”
Section: Cmos-mea Recordings Reveal a Link Between Cellular Electrica...supporting
confidence: 87%
“…We observed a high level of synchrony or correlation between voltage time-courses of islet electrodes, which are qualitatively similar to the synchrony in calcium measurements between beta-cells that has been previously reported and depends on gap junction coupling (23). Our network analysis demonstrated that islets have synchronized electrical activity (Figure 5B).…”
Section: Cmos-mea Recordings Reveal a Link Between Cellular Electrica...supporting
confidence: 87%
“…Indeed, possible structural long-range connections typically prevent propagating waves ( 88 ) and the combination of experimentally observed intercellular waves and small-world functional network properties speaks against a structural small-world substrate. Notably, further research also suggested that the small-world characteristics can in part be attributed to the multimodal nature of the oscillatory β cell activity, whereby the slow oscillatory component contributes more directly to long-range connectivity ( 54 ) and that the slow-activity-derived networks are less dependent on the structural gap junctional network ( 62 , 91 ). Furthermore, both modeling and experimental studies suggest that the intercellular waves and functional networks in a single focal plane are largely representative of the behavior in the islet as a whole ( 59 , 61 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gap junctional coupling of beta cells via Cx36 allows for the electrical linkage as well as the exchange of small molecules between neighboring cells and mediates principally the coherence of fast Ca 2+ dynamics ( 133 , 134 ). Correlations between slow Ca 2+ oscillations can be driven by metabolic coupling of neighboring cells, via feedback onto the slow dynamics by the fast dynamics due to same electrical coupling ( 77 , 135 139 ), as well as by intrinsic metabolic characteristics of beta cells ( 61 ). Since both fast and slow oscillations are synchronized among the cells in an islet, they both contribute to functional connectivity networks derived from Ca 2+ signals ( 56 , 133 , 140 , 141 ).…”
Section: Topological Analysis Of Functional Beta Cell Networkmentioning
confidence: 99%